Marketing plan for landmark Plaza Hotel Betong / Edward Michael Duk - Michael Duk, Edward (2003)
Proper and systematic marketing plan is a very important tool which can determine the success or failure of an organization. The main issue that is going to addressed in this study are the weakness and strength of Landmark Plaza Hotel, Betong, by conducting SWOT analysis. Direct interview with respondens and observation are the main method in collecting data for this study. Basically this study consists of introduction, current market situation, SWOT analysis, marketing strategy, action program, controls, conclusion as well as recommendation that must be taken by the hotel to further enhance its present as a market leader. The elevation of Betong District to Divisional status in 2002 require change in the mindset of existing business entities in Betong to face future challenges from new similar business through current evaluating of its strength and weakness to overcome short fall in the future. Lastly, although Landmark Plaza Hotel is currently doing well, a new and revised marketing plan is also important for it to sustain its market share in the hotel business.